2014
DOI: 10.1038/jp.2014.188
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-chain polyunsaturated fatty acids intake during pregnancy on adiposity of healthy full-term offspring at birth

Abstract: OBJECTIVE:The adjusted effect of long-chain polyunsaturated fatty acid (LCPUFA) intake during pregnancy on adiposity at birth of healthy full-term appropriate-for-gestational age neonates was evaluated. STUDY DESIGN: In a cross-sectional convenience sample of 100 mother and infant dyads, LCPUFA intake during pregnancy was assessed by food frequency questionnaire with nutrient intake calculated using Food Processor Plus. Linear regression models for neonatal body composition measurements, assessed by air displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…47 Nested within the same aforementioned cross-sectional study on 100 mother-infant pairs, the adjusted effect of longchain polyunsaturated fatty acid (LCPUFA) intake during pregnancy on the adiposity of offspring was also evaluated early after birth. 31 Positive associations were found between maternal docosahexaenoic acid intake and birth size in male offspring (β=0.165; 95% CI; 0.031 -0.299, p = 0.017), and between n-6 : n-3 LCPUFA ratio intake and adiposity in female offspring (β = 0.636; 95% CI; 0.125 -1.147, p = 0.016). 31 The association between offspring adiposity and maternal LCPUFA ratio intake favoring n-6 over n-3 LCPUFA is in coherence with the reported adipogenic effect of n-6 fatty acids family and anti-adipogenic effect of n-3 fatty acids family.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…47 Nested within the same aforementioned cross-sectional study on 100 mother-infant pairs, the adjusted effect of longchain polyunsaturated fatty acid (LCPUFA) intake during pregnancy on the adiposity of offspring was also evaluated early after birth. 31 Positive associations were found between maternal docosahexaenoic acid intake and birth size in male offspring (β=0.165; 95% CI; 0.031 -0.299, p = 0.017), and between n-6 : n-3 LCPUFA ratio intake and adiposity in female offspring (β = 0.636; 95% CI; 0.125 -1.147, p = 0.016). 31 The association between offspring adiposity and maternal LCPUFA ratio intake favoring n-6 over n-3 LCPUFA is in coherence with the reported adipogenic effect of n-6 fatty acids family and anti-adipogenic effect of n-3 fatty acids family.…”
mentioning
confidence: 95%
“…Two national official surveys on food availability including women of childbearing age, 19,20 seven national studies on the diet and nutritional status of women of childbearing age and pregnant women [21][22][23][24][25][26][27] and five national studies on the effect of maternal factors on their growing fetuses [28][29][30][31][32] were analyzed.…”
Section: Selected Studiesmentioning
confidence: 99%
“… 5 Moreover, n-3 LCPUFAs strongly affect fetal body composition. 6 Furthermore, a study conducted in Hong Kong reported that an average maternal consumption of 450 g of seafood per week during pregnancy could increase the IQ in the offspring. 7 …”
Section: Introductionmentioning
confidence: 99%
“…( 1 6 ) However, BW alone does not indicate an infant’s body composition (e.g., percent body fat), which may be a better predictor for adult-onset chronic diseases. ( 7 , 8 ) Preclinical studies have consistently shown correlations between high-fat maternal diets during pregnancy, altered fetal body composition, and metabolic syndrome in the offspring. The syndrome is characterized by insulin resistance, hypertension, dyslipidemia, and increased central adiposity.…”
Section: Introductionmentioning
confidence: 99%